2018
DOI: 10.1002/ppul.24038
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Robin sequence with cleft palate in the East of Scotland between 2004 and 2013

Abstract: RS incidence in EoS is substantially higher than that reported within other populations, and than previously reported in the UK. A possible association with intrauterine Methadone exposure warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 28 publications
3
28
0
Order By: Relevance
“…This population-based case-malformed control study covering almost 4 million births had a novel finding of a strong association between methadone exposure and PRS. These results provide an important confirmation of previous signals 10–12. In addition, we found raised ORs for cleft palate (aOR: 5.0 (95% CI 2.7 to 9.2)) and respiratory anomalies excluding PRS (aOR: 3.4 (95% CI 1.8 to 6.4)).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This population-based case-malformed control study covering almost 4 million births had a novel finding of a strong association between methadone exposure and PRS. These results provide an important confirmation of previous signals 10–12. In addition, we found raised ORs for cleft palate (aOR: 5.0 (95% CI 2.7 to 9.2)) and respiratory anomalies excluding PRS (aOR: 3.4 (95% CI 1.8 to 6.4)).…”
Section: Discussionsupporting
confidence: 91%
“…These independent data allowed a study with sufficient power to examine previously reported associations10–12 between methadone exposure and PRS, considering the rarity of the exposure-outcome combination. EUROCAT registries have previously been validated by examining associations between medications with known teratogenic effects and CA 27…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is now mostly considered a sequence of three main phenotypes: micrognathia (hypoplastic mandible), glossoptosis and upper airway obstruction (35)(36)(37). Its prevalence varies from 0.5 to 3.7 in 10000 births (8,(38)(39)(40) probably due to various diagnostic criteria applied and heterogeneity of characteristics (41)(42)(43). About 90% of the cases with PRS present also a cleft in the palate (44).…”
Section: Pierre Robin Sequencementioning
confidence: 99%